Teaching Standard English in the Trinidadian classroom thirty years after the Carrington-Borely report: A survey of recent trends and influences - Phillip-Peters, Sharon (School of Education, UWI, St. Augustine, 2008)
This paper examines the current status of teaching English in Trinidadian classrooms in the context of accepted L2 research, which holds that any programme aimed at teaching Standard English (SE) in the Anglophone Caribbean context should consider the students' L1, in this case Trinidadian Creole. The paper also surveys the changing dynamics of the language situation since the Carrington-Borely document, bringing to the fore classroom realities at the turn of the 21st century. The data for this case study of language usage are derived from students of one secondary school. Using examples of students' oral and written language, the study indicates that some of the structures that students use in speech often do not occur in their writing, suggesting that strategies used for targeting written SE may not always be as effective for targeting spoken Standard English. Given the uncoordinated attempts and the ambivalence of teachers in dealing with teaching issues, the paper posits that a clear statement of policy on teaching English in a Creole context, more classroom materials to support changing language scenarios, and the benefit of successful research experiments both at home and among Caribbean populations abroad would guide teachers' efforts toward more purposeful outcomes
Keywords: Language education; English; Teaching techniques; Trinidad and Tobago